Scientific Computation and Data Management Using Microsoft Windows Azure - Johnston, Steven; Cox, Simon; Takeda, Kenji (Grid and Cloud Database Management, 2011)
Cloud computing is the next stage in the evolution of computational and data handling infrastructure, establishing scale out from clients, to clusters to clouds. With the use of a case study, Microsoft Windows Azure has been applied to Space Situational Awareness (SSA) creating a system that is robust and scalable, demonstrating how to harness the capabilities of cloud computing. The generic aspects of cloud computing are discussed throughout.